Tindak Pidana Pencemaran Nama Baik di Muka Umum Terhadap Pejabat Negara (Studi Putusan Nomor:52/Pid.B/2020/PN Mjn) - Anisa Susilowati; Muhammad Khutub (UNES Law Review, 2023)
The crime of public defamation against a state official is an act that defames a person who serves as a state official (such as the President, Minister, Member of Parliament, etc.) with the aim of creating public distrust of the official. This action can be done in various ways, such as spreading false information, slander, or insults against the state official openly to the public. This research uses a normative method by examining Decision Number 52/Pid.B/2020/PN.Mjn in the case of Defamation. The results show that Article 310 of the Criminal Code is often used to punish individuals who want to reveal the truth, but have difficulties due to unclear defamation regulations. This is due to the lack of clarity in the concepts of "public interest" and "forced self-defense" contained in Article 310 paragraph 3 of the Criminal Code as a reason to waive criminal sanctions.